Assessment of bacterial dependence on marine primary production along a northern latitudinal gradient. Issue 10 (6th August 2018) - Fouilland, Eric; Floc'h, Emilie Le; Brennan, Debra; Bell, Elanor M; Lordsmith, Sian L; McNeill, Sharon; Mitchell, Elaine; Brand, Tim D; García-Martín, E Elena; Leakey, Raymond JG
ABSTRACT: Recent observations in polar marine waters have shown that a large fraction of primary production may be lost to respiration by planktonic bacteria due to very low bacterial growth efficiencies in cold waters. Here we report that sea temperature may be a key factor (but not the only one) influencing the interaction between bacteria and primary production in North Atlantic and Arctic waters, suggesting that low primary production rates could not sustain bacterial carbon demand in the coldest Arctic waters. The use of freshly produced phytoplankton exudate by bacteria in early- and mid-summer was assessed, together with the bacterial uptake of dissolved inorganic nitrogen (DIN = nitrate and ammonium), in surface waters along a latitudinal gradient from the North Sea to the Arctic sea ice. Bacterial production was independent of the low primary production measured in the coldest waters. Under these conditions, heterotrophic bacteria can consume a large fraction of DIN and N-rich organic matter, making them strong contributors to N fluxes in these waters. Abstract : Bacterial dependence on marine primary production.